Reflection on Easter During the Pandemic As The Church Today - Erlin Mayastuti; Fanni Margareta (Jurnal Teologi (JUTEOLOG), 2022)
This article will discusses the current phenomenon in the world, namely the Covid 19 pandemic, where we are faced with a condition where there is fear and worry about the future. Meanwhile, God’s church should be able to show its existence as God’s redeemed people and ther is no need to be afraid of anything in front of it even thoug it is death.The purpose of this article is to present a bliblical study of Passover celebration which is a journey of the Israelities out of the land of Egypt which has theologial implications regarding the resurrection and the death of the Lord Jesus Christ. This method used is historical anlysis of the Exodus text using an exposition approach and conduct an analysis with regard to context literary genre.The Passover event is an event which is an initiative from God to deliver the Israelities from Egypt. The conclusion that finding in this discussion is the momentum of the Easter celebration during the Covid 19 pandemic will increase the unity of heart and faith in the context of the church in Indonesia.